A Secure Framework based on Sensor Cloud Architecture for Efficient Street Monitoring in Smart Cities using Enhanced Elliptic Curve Encryption - Yadav, Rajan Kumar; Saran, Munish; Tripathi, Upendra Nath (International Journal of Computer Sciences and Engineering, 2024)
Smart City Surveillance systems play a key role in city development, helping to improve public safety and the efficiency of urban planning. But, there are some challenges regarding the security and integrity of the data transmitted from street cameras, such as privacy protection, legal compliance and protection from data breaches. Traditional methods such as access control lists offers coarse-grained data access and considering this as loophole our suggestion is Attribute-Based Encryption (ABE), which ensures fine-grained access control. We use Enhanced Elliptic Curve Cryptography (EECC) encryption on a sensor-cloud architecture, allowing data owners to define role-based access rules. This approach guarantees confidentiality and integrity and reduces computational overhead for faster encryption, decryption and key generation compared to traditional CP-ABE. This helps improve street camera security and is a step towards more resilient smart cities.